Effect of Amiodarone, Sotalol and Bisoprolol on Heart Rate Variability in Patients with Atrial Fibrillation - E. P. Popova (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2020)
Aim. To study the effect of class III antiarrhythmic drugs (amiodarone and sotalol), and the β-blocker bisoprolol on the spectral parameters of heart rate variability in patients with different forms of atrial fibrillation (AF).Material and methods. Spectral analysis of heart rate variability of 5-minute electrocardiography intervals was used. The study included patients with newly diagnosed AF and having a duration of the disease from 6 months to 8 years. Arterial hypertension, coronary artery disease, myocardial infarction (in history), conduction disorders and type 2 diabetes mellitus were diagnosed as comorbidities. The following parameters were calculated: the total power (TP) of the spectrum, the power of very low frequencies (VLF), low frequencies (LF) and high frequencies (HF).Results. In the group of patients with newly diagnosed AF without concomitant diseases after administration of amiodarone, VLF prevails in the spectrum structure, which indicates a significant role of humoral factors in the regulation of heart rate. The power of LF, reflecting the activity of the sympathetic nervous system, prevails over HF power after administration of amiodarone. In patients with newly diagnosed AF, having concomitant diseases, sympathetic influences prevail over parasympathetic ones by 3.6 times after administration of amiodarone. In the group of patients who have reduced the number of comorbidities, the LF/HF decreases and is only 1.66 after administration of amiodarone. The decrease in the number of negative factors is also accompanied by an increase in the influence of the vagus nerve on the activity of the heart. In the study of the effects of sotalol, the LF/HF in this group was twice lower in the group of patients with long-term AF. In patients receiving bisoprolol as antiarrhythmic therapy, the proportion of LF in the group of patients with newly diagnosed AF is 2 times lower, and the proportion of HF is twice higher than in the group of patients with long-term AF.Conclusion. The effect of antiarrhythmic drugs on the spectral parameters of heart rate variability depends on the duration AF. The presence of concomitant diseases of the cardiovascular system can significantly change the effect of antiarrhythmic drugs on the spectral parameters of heart rate variability and is accompanied by an increase in sympathetic activity. In patients with newly diagnosed AF, amiodarone and sotalol cause a similar effect – the predominance of sympathetic influence; when using bisoprolol, the predominant influence belongs to the vagus nerve. In patients with long-term AF, the opposite effect of drugs is observed: the use of amiodarone is accompanied by a more pronounced influence of the vagus nerve, and bisoprolol – the predominance of sympathetic influence. When using sotalol, sympathetic influences also prevail, more pronounced in patients with newly diagnosed AF.